Estimating gestational age using the anthropometric measurements of newborns in North Shewa Zone public hospitals, Oromia, Ethiopia - Dereje, Ifa; Awol, Mukemil; Getaye, Asfaw; Tujara, Zenebe; Alemu, Adugna; Negash, Abdi; Alemu, Fedasan; Zakir, Husen; Dinka, Ararsa; Edosa, Dejene; Shigign, Irean; Tunta, Abayneh; et al. (Frontiers in Pediatrics, 2023)
Background: Accurate estimation of gestational age is crucial to identify prematurity and other health problems of newborns and provide appropriate perinatal care. Although there are many methods of gestational age measurements, they are not always applicable. During these situations, it makes it difficult to know whether a baby is born preterm or not. Therefore, this study aimed to estimate gestational age using newborn anthropometric parameters.Purpose: To estimate gestational age using newborn anthropometric parameters in public Hospitals of North Shewa Zone, Oromia region, Ethiopia.: A facility based cross-sectional study was conducted from February 2022 to April 2022 using Interview based questionnaire and anthropometric measurements. The anthropometric parameters measured include Foot Length, Chest circumference, Mid Upper Arm Circumference, and Head Circumference. The total sample size for this study was 420. The data was cleaned, edited, checked for completeness manually and entered into Epi-data version 3.1 and then, transferred into SPSS for analysis. Descriptive analysis, Simple linear regression, and multiple linear regressions were used to analyze the data. Finally the data was presented using statements and tables. Results: All anthropometric parameters; Head circumference (r:0.483), MUAC (r:0.481), Foot length (r:0.457) and Chest Circumference (r:0.482) are significantly and positively correlated with gestational age. All anthropometric parameters were positive and significant estimates of gestational age. The combination of the four measurements had the strongest estimate of gestational age. Gestational age can be calculated by the formula: Gestational age (Weeks) = 9.78+ 0.209*CHC + 0.607*MUAC + 0.727*FL+ 0.322*HC.Gestational age can be measured using Head circumference, Mid-upper arm circumference, Foot length, and Chest circumference. Using the combination of the four anthropometric parameters is more powerful to estimate gestational age than using them individually. Therefore, recommend to use them when standard methods can't be applicable.